A Comparative Analysis of Preservice Teachers’ Knowledge of Reading Instruction and Their Confidence in Supporting Struggling Readers: A Study of India and England - Johny Daniel; Radhika Misquitta; Sophie Nelson (Education Sciences)
This study examines the knowledge and preparedness of preservice teachers in India and England regarding the teaching of foundational reading skills. Recognising the critical role of teachers in preventing reading difficulties through explicit instruction in phonics, vocabulary knowledge, and reading comprehension strategies, we aimed to compare preservice teachers’ knowledge in these areas between the two countries. A survey was developed for this study and administered to preservice teachers enrolled in teacher education programs in India and England. The survey assessed their phonics knowledge, pedagogical practices across key reading domains, and confidence in supporting students with reading difficulties in inclusive classrooms. Descriptive analyses indicated that English preservice teachers demonstrated greater familiarity with phonics knowledge and were better prepared in pedagogical practices, particularly in phonics instruction, phonological awareness, and reading fluency. Both groups showed low preparedness in teaching vocabulary knowledge. Notably, Indian preservice teachers reported higher confidence levels in supporting students with reading difficulties despite lower performance in knowledge assessments. These findings suggest a need for enhanced focus on explicit phonics instruction in Indian teacher education programs and increased emphasis on vocabulary instruction in both countries. Implications for early childhood education policy are discussed, particularly with regards to preparing teachers to provide high-quality literacy instruction that supports children’s academic success.